Analisis Pigmen dan Aktivitas Antibakteri In Vitro Pigmen Astaksantin Kepiting (Grapsus albolineatus Lamarck) Jantan - Aswan Thamin; Chairulwan Umar; Darussadah Paransa (Jurnal Perikanan Universitas Gadjah Mada, 2006)
Grapsus albolineatus is one of marine crustaceans which have carotenoid (astaxanthin) pigment. This research was conducted to analyze carotenoids (astaxanthin) extracted from G. albolineatus, and evaluate their in vitro antibacterial activity. The research was done in March-July 2002. Samples were collected from Manado Gulf, North Sulawesi. The result indicated that the carapace contained 4 carotenoids namely ß-caroten, ecinenon, astaxanthin diester, and astaxanthin monoester. In addition, the epidermis contained free astaxanthin. In vitro antibacterial activity test indicated that astaxanthin had low bacteriostatic activity against Psedomonas aeruginosa, Enterobacter cloacae, Staphylococcus aureus, and Proteus stuartii.